Errors in the prescription, preparation, and administration of medicines in Pediatric and Neonatal Intensive Care Unit: systematic review (Research, Society and Development, 2021)
Objective: To seek evidence on how to prevent potential medication errors in the prescription, preparation, and administration of medications for patients in the Pediatric and Neonatal Intensive Care Unit. Method: Systematic review and narrative synthesis. Results: 18 articles were selected with evidence on how to prevent potential medication errors in the prescription, preparation and administration of medications for patients in the Pediatric and Neonatal Intensive Care Unit. The studies are quite varied as to the methodology adopted. There are articles that made systematic, integrative, and narrative reviews, prospective and retrospective cohort studies, observational and economic analysis studies, most of them from European countries, not providing information on equity or subgroup analysis. Conclusion: There is evidence that structural and technological interventions; organizational and professional; regulatory and educational, and interdisciplinary and multifaceted, reduce prescription and preparation errors, drug interactions, adverse drug reactions, improving the quality of services and patient safety.